Event-by-Event Simulation of the Hanbury Brown-Twiss Experiment with Coherent Light (Communications in Computational Physics, 2010)
We present a computer simulation model for the Hanbury Brown-Twiss experimentthat is entirely particle-based and reproduces the results of wave theory. Themodel is solely based on experimental facts, satisfies Einstein's criterion of local causalityand does not require knowledge of the solution of a wave equation. The simulationmodel is fully consistent with earlier work and provides another demonstration thatit is possible to give a particle-only description of wave phenomena, rendering theconcept of wave-particle duality superfluous.